A strain-free semi-kinematic mount for ultra-precision optical systems. (November 2020) - Zhang, Defu; Li, Pengzhi; Xu, Wei; Li, Zongxuan; Jin, Guang; Zhang, Jianguo
Highlights: A high-precision and strain-free semi-kinematic mount has been proposed in the research for ultra-precision optical systems. For a lens with its diameter/thickness ratio of 6.73, a prototype of the semi-kinematic mount was developed. The experimental results show that the surface figure of the static mount is 1.963 nm before adhesion on the feet. The maximum error of the surface figure is only 0.2 nm when the translation position error of the lens is within 30 µm in x/y/z-axis direction or rotation position error of the lens is within 200µrad around x/y/z-axis, respectively, which reflects a good matching character between the semi-kinematic mount and the 6-DOF adjustment mechanism. With the action of the 312 mW thermal load, the surface figure degradation of the lens is less than 0.3 nm after reaching steady state, which indicates the design of the mount is almost strain-free. Abstract: A high-precision and strain-free semi-kinematic mount has been proposed in this research for ultra-precision optical systems. The mount includes three identical feet. Each foot constrains the axial and the tangential direction of the lens motion. Three feet in combination precisely control the six degree-of-freedom (6-DOF) motion of the lens. A strain-free mount of the lens was obtained and the high-precision surface figure of the lens was guaranteed. A prototype of the semi-kinematic mount was developed for the lens with diameter/thickness ratio of 6.73. The surface figure testing of the static mount, the 6-DOF dynamic adjustment and the thermal mount of the lens were carried out. The experimental results show that the surface figure of the static mount is 1.963 nm before adhesion on the feet. With the influence of the shrinkage stress of the epoxy glue, the surface figure of the lens is degenerated to 2.133 nm after adhesion on the feet. When the lens is adjusted 30 µm translation in x/y/z-axis direction or 200 µrad rotation around the x/y/z-axis, respectively, the maximum error of the surface figure is 0.2 nm, which implies the excellent matching character between the developed mount and the 6-DOF adjustment mechanism. Furthermore, with the action of 312 mW thermal load, the surface figure degradation of the lens is less than 0.3 nm in reaching steady state, which indicates the strain-free character of the mount. The experimental results verified the effectiveness of the proposed semi-kinematic mount, as well as its promising applications in ultra-precision optical systems.